Exon sequencing of the alpha-2-globin gene for the differential diagnosis of central cyanosis in newborns: a case report - Chungwoo Shin; Mee Hong; Myungshin Kim; Jung Hyun Lee (BMC, 2019)
Abstract Background Cyanosis is usually associated with serious conditions requiring urgent treatment in the neonatal intensive care unit (NICU). Hemoglobin M (Hb M) disease is one type of congenital methemoglobinemia characterized by cyanosis. Among these variants, α-globin chain mutations such as Hb M Boston present cyanosis from birth while other variants usually manifest later in life. Case presentation We report a case of a male newborn with cyanosis apparent since birth. Surprisingly, his respiratory and hemodynamic status including normal arterial blood oxygen saturation was stable, but oxygen saturation on pulse oximetry did not increase after 100% supplemental oxygen was started. In addition to routine pulmonary and cardiologic evaluation, further evaluation for dyshemoglobin was conducted; α2-globin gene sequencing showed a single-point variant causing Hb M Boston. Methemoglobin (MetHb) level estimated by co-oximetry was normal. After a 14-day stay in the NICU, the patient remained respiratory and hemodynamically stable without supplemental oxygen except for cyanosis. Conclusions Hb M disease is a benign disease and does not require any treatment whereas acquired methemoglobinemia is a potentially fatal condition. Neonatologists should be aware that low oxygenation status on pulse oximetry in the face of normal arterial blood saturation values might indicate the possibility of Hb M disease in early neonatal cyanosis, irrespective of MetHb value.